Auctions: Theory and practice - Klemperer, Paul (Princeton Princeton University Press, 2010)
Auctions: Theory and Practice provides a non-technical introduction to auction theory, and emphasises its practical application. Although there are many extremely successful auction markets, there have also been some notable fiascos, and Klemperer provides many examples. He discusses the successes and failures of the one-hundred-billion dollar "third-generation" mobile-phone license auctions; he, jointly with Ken Binmore, designed the first of these.
Keywords: Auctions; Economics; Third generation